Pleural Effusion During Tyrosine-Kinase Inhibitor (Imatinib) Treatment in Chronic Myeloid Leukemia - A Case Report - Brahmbhatt, Harshkumar; Nanda, Tarun; Prabhu, Pranam (Journal of Biomedical and Pharmaceutical Research, 2024)
Background: Chronic myeloid leukemia (CML) is effectively managed with tyrosine kinase inhibitors (TKIs) like imatinib. However, adverse effects such as pleural effusion, although rare, can complicate treatment. This report discusses a case of pleural effusion during imatinib therapy, highlighting the challenges and considerations in managing such complications. Methods: A single-case study was conducted at RNT Medical College, Udaipur, involving a CML patient who developed pleural effusion 18 months after starting imatinib. Diagnostic assessments included chest X-rays, CT scans, and thoracentesis. Results: Discontinuation of imatinib and symptomatic management led to the resolution of pleural effusion. The patient’s respiratory symptoms improved significantly with alternative management strategies for CML considered to avoid recurrence of the effusion. Conclusion: This case underscores the need for vigilant monitoring for adverse effects like pleural effusion in patients treated with TKIs. Early detection and appropriate management are crucial to prevent significant morbidity. Keywords: Chronic myeloid leukemia, Imatinib, Pleural effusion, Tyrosine kinase inhibitors, Case report